Incisional hernia after cesarean section: A systematic review. (January 2020) - Paulsen, Cecilie B; Zetner, Dennis; Rosenberg, Jacob
Abstract: Incisional hernia is a well-known complication following abdominal surgery. A frequently performed abdominal operative procedure is cesarean section. In 2015 the median cesarean section rate in Europe was 27 % with rates up to 57 % when looking at individual countries, and the rates of cesarean sections increased with 4 % in Europe from 2010 to 2015. Nonetheless, the occurrence of incisional hernia subsequent to cesarean sections is uncertain. The aim of this study was to investigate the reported occurrence of incisional hernia after cesarean section. We included original studies with women who had given birth at least once through a cesarean section. For studies to be eligible for inclusion, a minimum follow-up period of six months as well as a population of ten or more included patients were required. The primary outcome was occurrence of incisional hernia after cesarean section. The secondary outcomes were frequency of subsequent hernia operations, and if the hernia occurrence differed between midline and lower transverse incision, and between acute and elective cesarean section. Three databases were systematically searched: PubMed, Embase, and the Cochrane Library. The review was reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses-guideline (PRISMA) and registered with the international prospective register of systematic reviews (PROSPERO) (registration number: CRD42019129998). A total of 2170 potentially relevant studies were identified, and of these 28 studies were identified for full text screening. Five studies met the inclusion criteria comprising 275, 878 women with a previous cesarean section. The studies reported an occurrence of incisional hernia subsequent to cesarean section between 0.0–5.6 % with a follow-up time ranging from six months to ten years. Very few known risk factors for incisional hernia development were reported in the included studies. Overall, we found a low risk of incisional hernia subsequent to cesarean sections, even after a long follow-up period. Based on the included studies it was not feasible to estimate the occurrence of incisional hernia in different types of incisions, whether the urgency of the cesarean section affected the incisional hernia development, or to estimate the frequency of subsequent hernia repair. Further well-designed studies are therefore warranted.